Substitution of Concentrate by Ramie (Boehmeria nivea) Leaves Hay or Silage on Digestibility of Jawarandu Goat Ration - Despal; Mubarok; Ridla, M.; Permana, I.G.; Toharmat, T. (Pakistan Journal of Nutrition, 2017)
Background: The lower farmer profit margins that hinder ramie fiber plantation expansion can be overcome by utilizing the 82% of underutilized ramie plantation byproducts as ruminant feedstuffs. Although fresh ramie leaves are highly palatable for livestock, their availability is seasonal; therefore, the forage should be conserved. Objective: The aim of this study was to compare the capacity of silage and hay to conserved ramie biomass as a substitute for Jawarandu goat rations. Methodology: Three levels of treatments were tested, namely, a control ration (R1), a ration with 10% ramie silage (2) and a ration with 10% ramie hay (R3). Each treatment was repeated three times. Nine female Jawarandu goats with 27±4.68 kg initial body weight were used in this experiment. Feeds and nutrients offered, refused and excreted were measured to calculate feed and nutrient intake and digestibility. Results: The results showed that substitution of the concentrate with ramie leaves in the form of silage led to lower intake of feed and nutrients (Crude Protein (CP) and Nitrogen Free Extract (NFE)) and digestibility (dry matter (DMD), organic matter (OMD) and DCP). Substitution with ramie in the form of hay, however, increased digested feed and nutrient intakes. Although the ration contained ramie hay had a lower digestibility in comparison to the control ration, this could be recovered by the increased intake. Conclusion: Ramie leaves in the form of hay can be used to substitute 20% of the concentrate in Jawarandu goat rations or be included in 10% of total rations without any problem in availability of digested nutrients for the goat.